Effect of Arbuscular Mycorrhizal Fungi Inoculation on content and nutrient uptake of four-month-old Angsana (Pterocarpus indicus Willd.) plants in post-gold mining land in Bombana, Southeast Sulawesi - Asrianti Arif; Husna Husna; Faisal Danu Tuheteru; Indrawati Saleh; Albasri Albasri; Wiwin Rahmawati Nurdin; Parwito Parwito; Miranda Hadiyanti Hadijah (Journal of Tropical Mycorrhiza, 2023)
Mining activities are the main cause of nutrient-poor land and damage to soil physical properties. This condition also occurs in the post-Bombana gold mining area. thus negatively impacting plant growth response. Therefore, post-mining land remediation is carried out using environmentally friendly approaches such as Arbuscular Mycorrhizal Fungi and the use of adaptive local plant species such as Angsana (Pterocarpus indicus Willd.). This study aims to determine the levels and uptake of nutrients in the mycorrhizal P. indicus plant in post-gold mining field scale. Sampling was carried out in the laboratory of the Faculty of Forestry and Environmental Sciences, Halu Oleo University and observations of nutrient levels were carried out in the soil and plant laboratory of SEAMEO BIOTROP Bogor, this research was carried out for 3 months (May 2021). This research method used a Randomized Block Design (RAK) with 4 treatments, namely control, Glomus coronatum, G. claroideum and mixed AMF. The results showed that mixed AMF was effective in increasing N, Mn and Fe nutrient levels and G. claroideum increased P and K levels. Mixed AMF increased N, Mn and Fe nutrient levels and nutrient uptake in P. indicus plants four months old on the Bombana Gold Post Mining Land, Southeast Sulawesi.